Furanoterpenes, new types of protein tyrosine phosphatase 1B inhibitors, from two Indonesian marine sponges, Ircinia and Spongia spp. Issue 5 (1st March 2017) - Abdjul, Delfly B.; Yamazaki, Hiroyuki; Kanno, Syu-ichi; Wewengkang, Defny S.; Rotinsulu, Henki; Sumilat, Deiske A.; Ukai, Kazuyo; Kapojos, Magie M.; Namikoshi, Michio
Graphical abstract: Abstract: Protein tyrosine phosphatase (PTP) 1B negatively regulates the insulin and leptin signaling pathways, and, thus, the clinical application of PTP1B inhibitors to the prevention and treatment of type 2 diabetes and obesity is expected. During our studies on PTP1B inhibitors, two furanosesterterpenes and a C21 furanoterpene were obtained as new types of PTP1B inhibitors from two Indonesian marine sponges. (7 E, 12 E, 20 Z, 18 S )-Variabilin (1 ) and (12 E, 20 Z, 18 S )-8-hydroxyvariabilin (2 ) from Ircinia sp. and furospongin-1 (3 ) from Spongia sp. inhibited PTP1B activity with IC50 values of 1.5, 7.1, and 9.9 μM, respectively. The inhibitory activity of compound1 against T-cell PTP (TCPTP) was approximately 2-fold that against PTP1B, whereas the vaccinia H-1-related phosphatase (VHR) inhibitory effects of1 were 4-fold weaker than that of its PTP1B inhibitory activity. Compounds1 –3 at 50 μM did not show cytotoxicity against two human cancer cell lines, hepatoma Huh-7 and bladder carcinoma EJ-1. Compound1 did not enhance the phosphorylation level of Akt, a key downstream effector of the cascade, in Huh-7 cells.